2014
DOI: 10.1039/c3ce41856a
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening N⋯X halogen bonding via nitrogen substitution in the aromatic framework of halogen-substituted arylpyrazinamides

Abstract: The importance of N⋯X halogen bonding in a series of N-(5-halo-2-pyridinyl)pyrazine-2-carboxamides has been investigated by different methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Comparing the C–I stretching frequency of NMI-Py+TEG-I (1482 cm –1 ) with that of TEG-I (1485 cm –1 ) in water (Figure S9) confirmed the presence of X-bonding between NMI-Py and TEG-I in the construction of the supra-π-amphiphile. DFT optimized geometry of NMI-Py+TEG-I monomer revealed a N–I halogen bonding distance of 2.9 Å (Figure S10), which is comparable with the reported crystal structure data for N–I based halogen bonds . Unlike fibrillar morphology of NMI-Py+PEG-I , TEM images (Figure a, Figure S11) from an aqueous solution of NMI-Py+TEG-I revealed nearly spherical hollow structures, reminiscent of vesicle-like morphology with diameter in the range of 200–400 nm.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Comparing the C–I stretching frequency of NMI-Py+TEG-I (1482 cm –1 ) with that of TEG-I (1485 cm –1 ) in water (Figure S9) confirmed the presence of X-bonding between NMI-Py and TEG-I in the construction of the supra-π-amphiphile. DFT optimized geometry of NMI-Py+TEG-I monomer revealed a N–I halogen bonding distance of 2.9 Å (Figure S10), which is comparable with the reported crystal structure data for N–I based halogen bonds . Unlike fibrillar morphology of NMI-Py+PEG-I , TEM images (Figure a, Figure S11) from an aqueous solution of NMI-Py+TEG-I revealed nearly spherical hollow structures, reminiscent of vesicle-like morphology with diameter in the range of 200–400 nm.…”
Section: Resultssupporting
confidence: 80%
“…DFT optimized geometry of NMI-Py+TEG-I monomer revealed a N−I halogen bonding distance of 2.9 Å (Figure S10), which is comparable with the reported crystal structure data for N−I based halogen bonds. 50 Unlike fibrillar morphology of NMI-Py +PEG-I, TEM images (Figure 2a, Figure S11) from an aqueous solution of NMI-Py+TEG-I revealed nearly spherical hollow structures, reminiscent of vesicle-like morphology with diameter in the range of 200−400 nm. The particle size (D ∼ 350 nm) from variable-temperature (VT) dynamic light scattering (DLS) experiment (Figure S12) corroborated with the TEM results.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…The alternative approach is to increase the electron density of the halogen bond acceptor by the introduction of electron donating substituents. 63 A stronger halogen bond is often presumed to be reflected by a shorter distance between the halogen bond donor and the acceptor. 48 , 64 , 65 Computational studies revealed that the Hammett substituent constants of pyridine-based halogen bond acceptors correlate to the strength of their halogen bond.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the structures of N-(4-halophenyl)pyrazine-2-carboxamide and N-(5-halo-2-pyridinyl)pyrazine-2carboxamide suggests that the intramolecular N-HÁ Á ÁN(py) (py is pyridine) hydrogen-bonding interaction generates better coplanarity between the aromatic rings (Khavasi et al, 2014). In 6-fluoro-3-hydroxypyrazine-2-carboxamide, intramolecular O-HÁ Á ÁO hydrogen bonding, in addition to preventing keto-enol tautomerism of the hydroxy group, forms a six-membered ring motif.…”
Section: Pyrazine Derivatives and Their Available Donoracceptor Sitesmentioning
confidence: 99%